The role of ultrasonography in the diagnosis and management of chronic pancreatitis: Opportunities, limitations and prospects for development – a literature review - Pokrzepa, Jakub; Baran, Karolina; Bartnik, Katarzyna; Blecharz, Gabriela; Jankowska, Marlena; Jańczyk, Natalia; Mędrysa, Karolina; Presak, Michał; Szwech, Julia; Adamski, Jakub (Journal of Education, Health and Sport, 2025)
Introduction and purpose Chronic pancreatitis is a progressive disorder of the pancreas that may be caused by numerous factors. It leads to impaired nutrient absorption, diabetes development, chronic pain and an increased risk of pancreatic cancer development over the long term. Ultrasonography, both transabdominal and endoscopic, is a valuable diagnostic modality for CP, that provides good visualization of pathologic changes. A brief description of the state of knowledge The most common etiologies of chronic pancreatitis are alcohol consumption, smoking and genetic mutations. Ultrasound diagnostics, due to recent improvements in technology, enables early detection of the disease, making it possible to initiate treatment early enough, enhance the likelihood of its success and decrease the risk of complications, which include pseudocysts, duodenal stricture, splanchnic vein thrombosis and pancreatic cancer. The most common ultrasonographic findings in CP include dilatation of the main pancreatic duct, parenchymal calcifications, increased pancreatic volume, uneven contours, enlarged lymph nodes and the presence of free fluid in the abdominal cavity. Conclusions The findings above can be visualized using ultrasound techniques, including the least invasive and most accessible transabdominal ultrasound, endoscopic ultrasound, which enables the detection of pathologies at early disease stages, and emerging techniques such as elastography, which allows for the assessment of pancreatic fibrosis. Although there has been considerable improvement in ultrasound technology over the past few years, further development in the imaging modalities and the introduction of new, more precise guidelines and scoring systems is still required.